Host-directed antileishmanial interventions: Harvesting unripe fruits to reach fruition. (4th May 2023) - Seth, Anuradha; Kar, Susanta
Abstract: Leishmaniasis is an exemplary paradigm of immune evasion, fraught with the perils of limited clinical assistance, escalating costs of treatment and made worse with the lack of suitable vaccine. While drugs remain central to large-scale disease control, the growing emergence of parasite resistance necessitates the need for combination therapy involving host-directed immunological agents. Also, since prolonged disease progression is associated with strong immune suppression of the host, augmentation of host immunity via restoration of the immunoregulatory circuit involving antigen-presenting cells and T-cells, activation of macrophage function and/or CD4 + T helper 1 cell differentiation may serve as an ideal approach to resolve severe cases of leishmaniasis. As such, therapies that embody a synergistic approach that involve direct killing of the parasite in addition to elevating host immunity are likely to pave the way for widespread elimination of leishmaniasis in the future. With this review, we aim to recapitulate the various immunotherapeutic agents found to hold promise in antileishmanial treatment both in vitro and in vivo. These include parasite-specific antigens, dendritic cell-targeted therapy, recombinant inhibitors of various components intrinsic to immune cell signaling and agonists or antagonists to immune cells and cytokines. We also summarize their abilities to direct therapeutic skewing of the host cell-immune response and review their potential to combat the disease either alone, or as adjunct modalities. Graphical abstract: UF0001